1989
DOI: 10.1002/pros.2990150303
|View full text |Cite
|
Sign up to set email alerts
|

Conventional chemotherapeutic agents combined with DMSO or DFMO in treatment of rat prostate carcinoma

Abstract: Chemotherapy for prostatic carcinoma is usually reserved for those patients who have failed conventional therapy. These patients generally are in poor health and tolerate chemotherapy poorly. If doses of conventional agents could be decreased without altering cytotoxic activity, then conventional chemotherapy could become an attractive treatment modality. Dimethylsulfoxide and difluoromethylornithine have been shown to induce differentiation in some tumor systems. Growth alteration effects of these two agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cisplatin has previously been studied with DMSO in order to determine whether its anticancer effects are enhanced owing to the penetrant nature of DMSO (Pommier et al, 1988;Baliga et al, 1998). A study by Mickey et al (1989) showed that using low doses of cisplatin resulted in no cytotoxic effect on a tumour cell; however, on the addition of DMSO it caused severe toxicity. Repeating this with the addition of furosemide resulted in the killing of tumour cells without the toxicity problems.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin has previously been studied with DMSO in order to determine whether its anticancer effects are enhanced owing to the penetrant nature of DMSO (Pommier et al, 1988;Baliga et al, 1998). A study by Mickey et al (1989) showed that using low doses of cisplatin resulted in no cytotoxic effect on a tumour cell; however, on the addition of DMSO it caused severe toxicity. Repeating this with the addition of furosemide resulted in the killing of tumour cells without the toxicity problems.…”
Section: Introductionmentioning
confidence: 99%